2011
DOI: 10.4174/jkss.2011.81.5.316
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of parathyroid adenoma and papillary thyroid carcinoma

Abstract: PurposeAlthough several reports have been published regarding the coexistence of hyperparathyroidism and papillary thyroid carcinomas, concurrence of parathyroid adenoma and papillary thyroid carcinoma is extremely rare. The aim of this study was to describe experiences with concurrent parathyroid adenoma and papillary thyroid carcinoma.MethodsSeven patients with concurrent parathyroid adenoma and papillary thyroid carcinoma were identified between January 2006 and December 2007, and their medical records were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…Lee et al's report showed that primary hyperparathyroidism was diagnosed before thyroid carcinoma based on histopathology findings [13]. Therefore, our case was confirmed by histopathology after para-thyroidectomy.…”
Section: Discussionsupporting
confidence: 73%
“…Lee et al's report showed that primary hyperparathyroidism was diagnosed before thyroid carcinoma based on histopathology findings [13]. Therefore, our case was confirmed by histopathology after para-thyroidectomy.…”
Section: Discussionsupporting
confidence: 73%
“…One of the pathogenic factors invoked is the exposition to ionizing radiations: in irradiated patients, if a PHPT was present, a coexisting thyroid nodule was found in 95% of cases with a high incidence of thyroid carcinoma (30). In non-irradiated patients, both PTH and high serum calcium levels have been implicated in the pathogenesis of the non-medullary thyroid carcinoma (31)(32)(33). Anyway, this cancer should be carefully investigated because of its high frequency (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it should be considered that PHPT can coexist with thyroid carcinoma, especially the papillary form (PTC) (22)(23)(24). All considered, the presence of both pathologies simultaneously can lead to leave the hypercalcemia, a thyroid cancer or a toxic goiter untreated and can result in a reoperative approach (5).…”
mentioning
confidence: 99%
“…Some authors assumed the oncogenic effect of hypercalcaemia on the thyroid gland may be associated 15. In a recent retrospective study, Lee et al 5 summarised the concurrence of parathyroid adenoma and PTC on seven patients. Among them, no patient had the history of head or neck irradiation or surgeries.…”
Section: Discussionmentioning
confidence: 99%